Euphorbia Factor L2 ameliorates the Progression of K/BxN Serum-Induced Arthritis by Blocking TLR7 Mediated IRAK4/IKKβ/IRF5 and NF-kB Signaling Pathways - Tang, Jing; Cheng, Xiaolan; Yi, Shiyu; Zhang, Yuanyuan; Tang, Zhigang; Zhong, Yutong; Zhang, Qiuping; Pan, Bin; Luo, Yubin (Frontiers in Pharmacology, 2021)
Toll like receptor (TLR)s have a central role in regulating innate immunity and their activation have been highlighted in the pathogenesis of rheumatoid arthritis (RA). EFL2, one of diterpenoids derived from Euphorbia seeds, is nearly unknown expect for its improving effect on acute lung injury. Our present study aimed to investigate EFL2’s pharmacokinetic features, its therapeutic effect on rheumatoid arthritis, and explored the potential anti-arthritic mechanisms. K/BxN serum transfer arthritis (STA) murine model was used to assess EFL2’s anti-arthritic effects. We also applied UPLC-MS method to measure the concentrations of EFL2 in plasma. The inhibitory effects of this compound on inflammatory cells infiltration and activation were determined by flow cytometry analysis and quantitative real-time polymerase chain reaction (qRT-PCR) in vivo, and immunochemistry staining and ELISA in murine macrophages and human PBMCs in vitro, respectively. The mechanism of EFL2 on TLRs mediated signaling pathway was evaluated by PCR array, Western blot, plasmid transfection and confocal observation. Intraperitoneal (i.p.) injection of EFL2, instead of oral administration, could effectively ameliorate arthritis severity of STA mice. The inflammatory cells migration and infiltration into ankles were also significantly blocked by EFL2, accompanied with dramatically reduction of chemokines mRNA expression and pro-inflammatory cytokines production. In vivo PCR microarray indicated that EFL2 exerted anti-arthritis bioactivity by suppressing TLR7 mediated signaling pathway. In vitro study confirmed the inhibitory effects of EFL2 on TLR7 or TLR3/7 synergistically induced inflammatory cytokines secretion in murine macrophages and human PBMCs. In terms of molecular mechanism, we further verified that EFL2 robustly downregulated TLR7 mediated IRAK4-IKKb-IRF5 and NF-kB signaling activation, and blocked IRF5 and p65 phosphorylation and translocation activity. Taken together, our data indicate EFL2’s therapeutic potential as a candidate for rheumatoid arthritis and other TLR7-dependent diseases.